2010
DOI: 10.1007/s10344-010-0441-6
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of wild boar females in Portugal

Abstract: Reproductive tracts of 214 female wild boars collected in Central Portugal between October and February over the period 1997 to 2001 were examined. From this material, we were able to determine reproductive phenology (conception and birth periods) as well as age and weight of sows at puberty, ovulation rates of adults, foetal sex ratio, levels of intrauterine mortality, final litter size and postnatal mortality. Differences between year, region, age and body weight were analysed. A total of 66.8% of the female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 14 publications
4
46
0
Order By: Relevance
“…At that time, the proliferation process slows down and apoptosis is enhanced, i.e. there is a negative correlation between ZEN concentrations and ovulatory activity because anoestrus in female boars is generally observed in spring and summer (Fonseca et al 2011). After farrowing, mothers have to feed their offspring at a time when food is scarce, at least in the initial period.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, the proliferation process slows down and apoptosis is enhanced, i.e. there is a negative correlation between ZEN concentrations and ovulatory activity because anoestrus in female boars is generally observed in spring and summer (Fonseca et al 2011). After farrowing, mothers have to feed their offspring at a time when food is scarce, at least in the initial period.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found a positive relationship between female age or body weight and the number of foetuses per female (Aumaître et al, 1982;Fernández-Llario et al, 1999;Fonseca et al, 2011). Also environmental factors (weather conditions and food resources) influenced the reproduction of wild boar (Bieber and Ruf, 2005;Fernández-Llario and Mateos-Quesada, 2005;Geisser and Reyer, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…It shows sexual size dimorphism (Focardi et al, 2008) and a low natural adult mortality rate in temperate climes (Keuling et al, 2013a), which is typical for Kstrategists. On the other hand, it has by far the highest reproductive potential and fecundity of all ungulate species world-wide in relation to its body mass (Boitani et al, 1995b;Focardi et al, 2008;Fonseca et al, 2011;Gaillard et al, 1993;Servanty et al, 2009), so that it can reach high population densities within a very short time period (Geisser and Reyer, 2005). Additionally, it is also an opportunistic omnivore with a high adaptability to changing environmental conditions (Baubet et al, 2004;Gamelon et al, 2013;Schley and Roper, 2003;Servanty et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, hunting and trapping could lead to adaptation of wild boar behaviour, for instance by becoming more active during the night, increased home range sizes (Calenge et al, 2002;Sodeikat and Polheimer, 2002;Scillitani et al, 2010) and/or increased reproduction (Bieber and Ruf, 2005;Hanson et al 2009;Gamelon et al, 2011;Servanty et al, 2011). In addition, an increase in effort is required to hunt or trap wild boar when the animal density reduces (Cruz et al, 2005), but maintaining an intense hunting or trapping pressure during several seasons could be difficult for practical and/or social reasons (Fonseca et al, 2011;Boadella et al, 2012). No papers could be found which reported the time period over which population reductions could be maintained in Europe.…”
Section: Literature Reviewmentioning
confidence: 99%